Measuring Trends in Leisure: The Allocation of Time Over Five Decades - Aguiar, M.; Hurst, E. (Quarterly Journal of Economics, 2007)
In this paper, we use five decades of time-use surveys to document trends in the allocation of time within the United States. We find that a dramatic increase in leisure time lies behind the relatively stable number of market hours worked between 1965 and 2003. Specifically, using a variety of definitions for leisure, we show that leisure for men increased by roughly six to nine hours per week (driven by a decline in market work hours) and for women by roughly four to eight hours per week (driven by a decline in home production work hours). Lastly, we document a growing inequality in leisure that is the mirror image of the growing inequality of wages and expenditures, making welfare calculation based solely on the latter series incomplete.